Relationship between Lung Function and Metabolic Syndrome - Chen, Wei-Liang; Wang, Chung-Ching; Wu, Li-Wei; Kao, Tung-Wei; Chan, James Yi-Hsin; Chen, Ying-Jen; Yang, Ya-Hui; Chang, Yaw-Wen; Peng, Tao-Chun (PloS one, 2014)
Although the link between impaired lung function and cardiovascular events and type 2 diabetes mellitus has been recognized, the association between impaired lung function and metabolic syndrome has not been comprehensively assessed in the United States (U.S.) population. The aim of our study was to explore the association between impaired lung function and metabolic syndrome in a nationally representative sample of men and women. This cross-sectional population-based study included 8602 participants aged 20-65 years in the Third National Health and Nutrition Examination Survey (NHANES III). We examined the relationship between the different features of metabolic syndrome and lung function, including forced vital capacity (FVC) and forced expiratory volume in 1 second (FEV1). After adjusting for potential confounders such as age, body mass index, inflammatory factors, medical condition, and smoking status, participants with more components of metabolic syndrome had lower predicted values of FVC and FEV1 (p for trend <0.001 for both). Impaired pulmonary function was also associated with individual components of metabolic syndrome, such as abdominal obesity, high blood pressure, high triglycerides, and low high density lipoprotein (HDL) cholesterol (p<0.05 for all parameters). These results from a nationally representative sample of US adults suggest that a greater number of features of metabolic syndrome is strongly associated with poorer FVC and FEV1. In clinical practice, more comprehensive management strategies to address subjects with metabolic syndrome and impaired lung function need to be developed and investigated.